2017
DOI: 10.26509/frbc-ec-201721
|View full text |Cite
|
Sign up to set email alerts
|

Have Inflation Dynamics Changed?

Abstract: Using a flexible statistical model to project inflation outcomes into the future, this Commentary finds that the most likely path for inflation based on recent inflation dynamics is generally similar to what would have been expected given inflation dynamics in the late 1990s, but there is more uncertainty around the forecast now than in the late 1990s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…In this analysis, we estimate a version of model iii where we make the model have very close to no time variation for the coefficients on the (contemporaneous and lagged) unemployment rate in the inflation equation; this is achieved by placing very tight priors on the relevant elements in 𝚺 𝜽 , thereby in practice making them zero. Marginal likelihood calculations for this model show that the log marginal likelihood is lower (−81.8) than that of the original version of model iii presented in Table1.15 Comparing our estimates in Figure4to the findings from a few other recent studies, it can be noted thatBlanchard et al (2015) found a somewhat steeper Phillips curve for the United States; estimating a single-equation regression model with constant parameters employing quarterly data from 1990 to 2014 -and a shorter subsample ranging from 2007 to 2014 -the estimated slope was around −0.25 Knotek and Zaman (2017). report estimates from just two points in time from their BVAR with time-varying parameters -1999Q3 and 2017Q3 -both of which are associated with a quite modest slope (−0.07 and −0.06, respectively).…”
supporting
confidence: 58%
See 3 more Smart Citations
“…In this analysis, we estimate a version of model iii where we make the model have very close to no time variation for the coefficients on the (contemporaneous and lagged) unemployment rate in the inflation equation; this is achieved by placing very tight priors on the relevant elements in 𝚺 𝜽 , thereby in practice making them zero. Marginal likelihood calculations for this model show that the log marginal likelihood is lower (−81.8) than that of the original version of model iii presented in Table1.15 Comparing our estimates in Figure4to the findings from a few other recent studies, it can be noted thatBlanchard et al (2015) found a somewhat steeper Phillips curve for the United States; estimating a single-equation regression model with constant parameters employing quarterly data from 1990 to 2014 -and a shorter subsample ranging from 2007 to 2014 -the estimated slope was around −0.25 Knotek and Zaman (2017). report estimates from just two points in time from their BVAR with time-varying parameters -1999Q3 and 2017Q3 -both of which are associated with a quite modest slope (−0.07 and −0.06, respectively).…”
supporting
confidence: 58%
“…By doing this, we reduce the risk that important dynamic effects between the two variables are omitted. Reflecting upon our modelling choice at a more general level, using sparse specifications is of course not something new in the literature related to the Phillips curve; see, for example, parts of the analysis in Stock and Watson (1999) and Faust and Wright (2013), or the contributions by Clark and McCracken (2006), Chan et al (2016), Dotsey et al (2018), Knotek and Zaman (2017), Alexius et al (2020), and Karlsson and Österholm (2020b) in which only small models are used. It does, however, stand in contrast to literature relying on larger models, such as LasĂŠen and Taheri Sanjani (2016).…”
Section: Methodological Frameworkmentioning
confidence: 99%
See 2 more Smart Citations